The role of the immune system in regression of the bovine corpus luteum - Anderson, Lesley Ann (The University of Edinburgh, 1998)
In recent years there has been increasing interest in the role of the immune system in reproductive physiology. The aim of this study was to quantify immune cell populations within the cow corpus luteum (CL) throughout the oestrous cycle in order to investigate whether these cells could be involved in controlling luteal function, particularly around the time of luteolysis. Although prostaglandin F2a (PGF₂α) released from the uterus is known to be the luteolytic substance in the cow, events occurring at the level of the CL at this time are less clearly defined. Immune cells and their cytokine products have significant potential to influence the cells of the CL at luteolysis

Six CL were collected from each of four stages of the oestrous cycle, identified on the basis of their gross appearance, for preliminary immunohistochemical studies. Immune cell populations and MHC II expression varied throughout the oestrous cycle. In particular, the number of macrophages, T-lymphocytes (CD5+, CD4+) and MHC II expression was significantly higher in late stage CL (after luteolysis) compared to all other stages. To study in more detail the cellular events associated with luteolysis, the oestrous cycles of 19 cows were synchronised. CL were collected between days 16 and 20 of the following oestrous cycle. A significant increase in the number of Tlymphocytes (CD5+, CD8+) was detected in CL collected from day 16 onwards, compared to days 13-14. This increase occurred prior to functional luteolysis. Artificially-induced luteolysis was then assessed as a potential model for further studies around luteolysis. CL collected 6, 12 and 24 hours after luteolysis, induced using a single injection of 25mg PGF₂α, had undergone dramatic structural regression which bore little resemblance to events during normal luteolysis and so this model was rejected. The role of endogenous PGF₂α in inducing the influx of T-lymphocytes was then investigated. Production of PGF₂α was inhibited in 12 cows between days 15 and 18 of the oestrous cycle and artificially replaced in six cows for 24 hours before collection of the C.L on day 18. The number of macrophages was significantly lower in all animals in which PGF2a was inhibited compared to control animals but Tlymphocyte numbers were not significantly altered

Cytokine production within the CL was also studied using the reverse trancriptase polymerase chain reaction (RT-PCR). Tumour necrosis factor-a, (TNF-α), interleukin1ß (II-Iß (3) and interferon-γ (IFN-γ) were detectable in similar amounts in CL at all stages of the oestrous cycle and after induced luteolysis and PGF₂α inhibition. Monocyte chemoattractant protein-1 (MCP-1) was higher in CL from animals after functional luteolysis compared to CL collected prior to luteolysis but the increase occurred before macrophage numbers in the CL increased. MCP-1 may be involved in chemotaxis of monocytes into the CL during luteal regression.

In conclusion, these results provide further evidence of a role for immune cells, particularly T-lymphocytes, in controlling CL function, outwith their involvement in structural luteolysis. Increasing concentrations of PGF₂α may be one of the major factors influencing the presence of macrophages, and possibly other immune cells, in luteal tissue. The presence of mRNA for TNF-α, IL-1ß, IFN-γ and MCP-1 at all stages studied indicates a potential role for these substances in the CL although more detailed investigations are required. MCP-1 appears to have a specific involvement in the chemotaxis of monocytes to the CL in preparation for structural regression.